Seed Sovereignty Struggles in an Emberá-Chamí Community in Colombia (Alternautas, 2022)
Laura Gutierrez’ article takes us to Riosucio, in the North West of Colombia, where the Embera-Chami indigenous people of the region have organised to promote and protect their agricultural sovereignty. Laura examines the intricacies of the seed conflicts that take place in this country, where the government and industrial agriculture associations have promoted the use of certified seeds, while Embera-Chami communities have challenged this system through the development of their own networks of seed saving, multiplication, and reproduction. These conflicts constitute struggles over seed sovereignty, that is, over the way seeds are produced, owned, circulated, saved, and endowed with meanings and spirituality. However, these struggles reveal a larger battle over autonomy and place-based ways of inhabiting and sustaining territory. These conflicts are the manifestation of the coloniality of power that continues to promote Euro-American models and knowledges as superior, and Latin American agricultural and botanical knowledges as inferior. The seed, as a living organism that interacts with humans, and as a recipient of cultural, symbolic, and economic values, is at the core of the struggle between colonialism and local resistance, and thus serves as a lens through which these conflicts can be analysed.